2010
DOI: 10.4103/0975-1483.63144
|View full text |Cite
|
Sign up to set email alerts
|

Studies on In situ Hydrogel: A Smart Way for Safe and Sustained Ocular Drug Delivery

Abstract: The present work describes the formulation development of ophthalmic in situ gelling system using thermo-reversible gelling polymer, i.e. Pluronic F 127 (PF127). Because of high concentration (20 to 25%w/v) of this polymer required for in situ gelation causes irritation to the eye. So, to reduce this concentration, an attempt was made to combine the PF127 with other polymers like hydroxy propyl methyl cellulose (HPMC) as a viscosity increasing agent or with polymers like carbopol 940, xanthan gum, and sodium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 11 publications
0
28
0
Order By: Relevance
“…In situ gels are a drug delivery system which when administered in a liquid form phase shift into a gel or solid form once reaching the conjunctival cul-de-sac. [39] Despite typically being administered [1,4] ) 2 Ability to modify the rate of release of drug [1,4] 3 Ability to provide a stimuli-sensitive drug release mechanism [1,4] 1 Allow sustained release of drug [35,36] 2 Prolonged therapeutic duration at site of action [35,36] 3 Can overcome limitation of eye drops where drug wastage is an issue [35,36] 1 No blurred vision or irritation with administration [39,40] 2 Prolonged drug retention at desired tissue in the eye [39,41] 3 Decreased frequency of dosing [40,41] 1 Both hydrophilic or lipophilic drugs can be used [32] 2 Increase drug penetration across conjunctival and corneal epithelium [32] 3 Display ability to provide sustained released [32,46] 4 Decreased frequency of dosing [46] Cons 1 Low reproducibility [4,48] 2 Instability of the macromolecules during production stage [4,48] 3 Variable size distribution [4,48] 4 Expensive [4,48] 1 May increase intraocular pressure and induce local systemic adverse effects [38] 2 Inconvenient administration for patient [38] 3 Risk of tissue damage if administered incorrectly [38] 1 Lack of cell specificity [41] 2 Requires intravitreal administration due to poor penetration & specificity [40] 3 Expensive …”
Section: Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ gels are a drug delivery system which when administered in a liquid form phase shift into a gel or solid form once reaching the conjunctival cul-de-sac. [39] Despite typically being administered [1,4] ) 2 Ability to modify the rate of release of drug [1,4] 3 Ability to provide a stimuli-sensitive drug release mechanism [1,4] 1 Allow sustained release of drug [35,36] 2 Prolonged therapeutic duration at site of action [35,36] 3 Can overcome limitation of eye drops where drug wastage is an issue [35,36] 1 No blurred vision or irritation with administration [39,40] 2 Prolonged drug retention at desired tissue in the eye [39,41] 3 Decreased frequency of dosing [40,41] 1 Both hydrophilic or lipophilic drugs can be used [32] 2 Increase drug penetration across conjunctival and corneal epithelium [32] 3 Display ability to provide sustained released [32,46] 4 Decreased frequency of dosing [46] Cons 1 Low reproducibility [4,48] 2 Instability of the macromolecules during production stage [4,48] 3 Variable size distribution [4,48] 4 Expensive [4,48] 1 May increase intraocular pressure and induce local systemic adverse effects [38] 2 Inconvenient administration for patient [38] 3 Risk of tissue damage if administered incorrectly [38] 1 Lack of cell specificity [41] 2 Requires intravitreal administration due to poor penetration & specificity [40] 3 Expensive …”
Section: Liposomesmentioning
confidence: 99%
“…Consequently, there is a reduced frequency of administration that can reduce the risks associated with ocular procedures. [39,41] Despite these benefits, a significant limitation currently for in situ gels is the cost for administration, especially for implants. Additionally, when applied topically, patients may experience temporary blurred vision.…”
Section: Liposomesmentioning
confidence: 99%
“…Viscosities were determined at different shear rates from 00 to 100 rpm using suitable spindle number1. 16 The measurements on each sol were performed in triplicate.…”
Section: Measurement Of Rheological Properties Of Igss 16mentioning
confidence: 99%
“…The study suggested that by combining Pluronic F127 with other in situ gelling or viscosity enhancing polymers, not only the concentration of Pluronic F127 can be reduced from 25% to 15% w/v but also the individual polymer concentrations (i.e. carbomer and sodium alginate) can also be reduced without compromising the in vitro gelation capacity as well as overall rheology of the system [47]. Kumar et al [48], developed an in situ gelling ocular drug delivery system based on combination of methylcellulose or HPMC and Carbopol to reduce the total polymer content of the formulation.…”
Section: Combination Of Polymers Having Different Gelation Mechanismsmentioning
confidence: 99%
“…Thus to reduce the concentration of Pluronic F127, Shastri et al [47], combined it with polymers like HPMC as a viscosity increasing agent or with polymers such as Carbopol 940, xanthan gum, and sodium alginate (high glucuronic acid content) for pH and cation-triggered sol-gel transition, respectively. The study suggested that by combining Pluronic F127 with other in situ gelling or viscosity enhancing polymers, not only the concentration of Pluronic F127 can be reduced from 25% to 15% w/v but also the individual polymer concentrations (i.e.…”
Section: Combination Of Polymers Having Different Gelation Mechanismsmentioning
confidence: 99%